Karakterisasi Deposit Mineral Zeolit Dalam Aspek Pemanfaatannya di Bidang Pertanian - Astiana Sastiono (Jurnal Ilmu Pertanian Indonesia, 1991)
Agricultural extensification effort in Indonesia are almost always accompanied by a problem of low productivity land. This problem is caused by physical or chemical properties of the land, such as cation exchange capacity, base, pH, nutrient availability, and low water absorbtion capacity, while Al and Fe saturation are relatively high. Utilization of zeolite mineral is an alternative method besides lime in order to improve land quality, and to increase agricultural production. The aim of this research is to identify characteristics of zeolite from some deposits that have high relation to its uses as a cation - exchange substance or as an absorbent of water and nutrients. Zeolite of Bayah has the highest purity compare with that of Bojong and Gunung Dewi. The best heating - activation result according to X-ray diffractogram and zeolite CEC is the temperature between 150 - 300C, while dealumination-activation with HCI of0.2 - 0.5 N can improve zeolite capability as a cation exchange substance. Fraction coarser than 28 mesh to 60 mesh gives better utilization than that of finer ones. Fraction of 48 mesh with 150 - 300C heat treatment gives the highest absoptive capacity to water.